Impact of Device Area and Film Thickness on Performance of Sol-Gel Processed ZrO2 RRAM - Lee, Sojeong; Kim, Taegyun; Jang, Bongho; Lee, Won-Yong; Song, Kyu Chan; Kim, Hyun Seo; Do, Gyung Yeop; Hwang, Seung Bum; Chung, Seungjun; Jang, Jaewon (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
Asol-gel-processed ZrO2 layerwas used as an active layer for a resistive random-accessmemory (RRAM). With top Ag electrodes, the fabricated devices show convention albipolar switching memory properties. The impacts of device size and ZrO2 film thickness on device performance were investigated. The scaling of the device area and the successful increase in ZrO2 film thickness increased the high-resistance state (HRS)/low-resistance state (LRS) ratio values and improved the non-volatile memory properties, such as retention and endurance. The fabricated ITO/ZrO2/Ag RRAM shows good retention and endurance properties. The HRS and LRS were found to last for 10(4) s without any significant degradation.
Keywords: RESISTANCE; TRANSISTORS